Report of chronic myeloid leukemia in chronic phase from Dr. Senthil Rajappa, 2002-2009 - Rajappa, Senthil; Varadpande, Lalit; Paul, Tara Roshni; Jacob, Rachel Thomas; Digumarti, Raghunadharao (Indian Journal of Medical and Paediatric Oncology, 2013)
Nizam′s Institute of Medical Science is a premier institute of Hyderabad, established in 1980. The Medical Oncology Unit is the 1 st comprehensive cancer center established for the state of Andhra Pradesh. The department has presented a data of total 201 patients with the median age of 32 at diagnosis. Among these 66 (33%) patients belonged to low Hasford risk group. Complete hematologic response was seen in 195 (97%) of patients. The progression free survival (PFS) was 77% for all patients while those who achieved complete cytogenetic response, PFS was 88% at 29 months.
Keywords: Chronic myeloid leukemia; chronic phase; imatinib